Alternative RNA splicing: contribution to pain and potential therapeutic strategy - Donaldson, Lucy F.; Beazley-Long, Nicholas (Elsevier, 2016)
Since the sequencing of metazoan genomes began, it has become clear that the number of expressed proteins far exceeds the number of genes. It is now estimated that greater up to 98% of human genes give rise to multiple proteins through alternative pre-mRNA splicing. This review highlights the known alternative splice variants of many channels, receptors and growth factors important in nociception and pain. Recently, pharmacological control of alternative splicing has been proposed as potential therapy in cancer, wet age-related macular degeneration, retroviral infections and pain. In this review we consider the effects that known splice variants of molecules key to nociception/pain have on nociceptive processing and/or analgesic action, and the potential for control of alternative pre-mRNA splicing as a novel analgesic strategy.